Educational trails of the Racławka Valley Nature Reserve and their potential for geoeducation - Szreter, Anna; Skoczylas-Śniaz, Sylwia; Wierzba, Katarzyna; Czoch, Paulina; Bolek, Szymon; Kowal-Kasprzyk, Justyna (Geotourism/Geoturystyka, 2023)
The Racławka Valley is located west of Krakow, in the Krakow-Częstochowa Upland. This is a place of high bio- and geodiversity, where various rocks of different ages outcrop in vast excavation pits, narrow gorges or form characteristic monadnocks. The richness of various morphological forms and special habitats led to the constitution of a nature reserve, covering most of the Racławka Valley and adjacent, southern parts of the Szklarka Valley. Three educational trails lead through the reserve, connecting a number of geosites. The Geotourism Students’ Scientific Club (GSSC) from AGH University of Science and Technology examined the usability of these trails for geoeducation. After completing geotourism valorisation, adequate teaching materials were prepared, and different age groups were guided around the trails. Their comprehension has been verified by quizzes and opinions gathered through questionnaires. On the bases of these, the three educational trails were widely described and assessed in respect for their terrain difficulty, accessibility, and infrastructure. Each trail has a leitmotif and a specific theme, however geosites from different trails can be combined together to get a route of a chosen theme. The GSSC also released three new geotourism guidebooks, one for each trail, as a result of AGH rector’s grant projects in the years 2018–2020.